In-service elementary classroom teachers training in the pedagogical use of technologies in music education - Milhano, Sandrina (2022)
The importance of training in the pedagogical use of technology in the professional development of future elementary school teachers retains a special significance with the current impacts of the COVID-19 on pedagogical practices. The use of technology in primary schools is assumed in the Portuguese curricula and is part of teacher training. However, not all elementary school teachers and future teachers have the confidence and the competencies to implement it in music education classes or to embrace its use in virtual classrooms. The training underlining the professional learning of in-service elementary classroom teachers needed to be adapted to support further future teachers in creating new forms to build significant learning and teaching processes. The current paper seeks to identify in-service elementary classroom teachers learning development needs to better adapt their music education practices at school using technology. In-service elementary Portuguese teachers (16) responded to a questionnaire regarding their difficulties and training needs to better adapt their music education practices at school to online, synchronous and asynchronous strategies and activities. They suggest that some pedagogical competencies in the use of technology in their classes with children are associated with their use of technology as part of their training and most seem to have adapted to the current use of technologies in class. In-service teachers also indicate the need for further development regarding music education pedagogical topics such as strategies to promote their children music learning, learning processes assessment, and integrated approaches to the school curriculum. They expect these pedagogical topics associated with technology requirements in music education to continue as part of their current training in addition to continuous professional learning opportunities.